2013
DOI: 10.1638/2012-0022r.1
|View full text |Cite
|
Sign up to set email alerts
|

ANAEROBIC AND AEROBIC BACTERIOLOGY OF THE SALIVA AND GINGIVA FROM 16 CAPTIVE KOMODO DRAGONS (VARANUS KOMODOENSIS): NEW IMPLICATIONS FOR THE “BACTERIA AS VENOM” MODEL

Abstract: It has been speculated that the oral flora of the Komodo dragon (Varanus komodoensis) exerts a lethal effect on its prey; yet, scant information about their specific oral flora bacteriology, especially anaerobes, exists. Consequently, the aerobic and anaerobic oral bacteriology of 16 captive Komodo dragons (10 adults and six neonates), aged 2-17 yr for adults and 7-10 days for neonates, from three U.S. zoos were studied. Saliva and gingival samples were collected by zoo personnel, inoculated into anaerobic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
3
23
0
3
Order By: Relevance
“…Multiple authors have cast their doubt upon the "bacteria as venom" model. 3,6,7 The bacterial flora isolated from their mouths may reflect bacteria acquired from environmental sources or from feeding on carrion, which is known as the "passive acquisition" model. 3 There are other factors that contribute to the lethality of Komodo dragons.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple authors have cast their doubt upon the "bacteria as venom" model. 3,6,7 The bacterial flora isolated from their mouths may reflect bacteria acquired from environmental sources or from feeding on carrion, which is known as the "passive acquisition" model. 3 There are other factors that contribute to the lethality of Komodo dragons.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic bacteria have also been reported in the saliva of the Komodo dragon (Auffenberg, 1981;Montgomery et al, 2002), and interdenticular sulci may help the proliferation and entering of these toxic bacteria within the prey. Fry et al (2009), however, note that no compelling evidence supports the presence of pathogenic bacteria in the saliva of Varanus komodoensis, a hypothesis supported by Goldstein et al (2013) based on captive Komodo dragons. Yet, Tehrani et al (2008) and Vikrant and Verma (2014) have reported septic effects of varanid bites, and pathogenic bacteria might, therefore, be present and possibly hosted within interdenticular sulci of the crowns of wild varanids.…”
Section: Interdenticular Sulcimentioning
confidence: 97%
“…The saliva of wild Komodo dragons is thought to contain many different strains of bacteria, some of which are known to cause sepsis. 14, 15 However, this bacteria-laden saliva never sickens the Komodo dragon. Investigators therefore hypothesized that proteins in the dragon's saliva or blood might provide immunity.…”
Section: Introductionmentioning
confidence: 99%